EKSISTENSI PEREMPUAN DALAM SERIAL GADIS KRETEK: KAJIAN FEMINISME EKSISTENSIALIS SIMONE DE BEAUVOIR - Syahrina Adella; Elisa Maharani Siahaan; Nur Rizkia Fazira; Muhammad Anggie Januarsyah Daulay (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This study explores the portrayal of women's existence in the 2023 series Gadis Kretek through the lens of Simone de Beauvoir's existentialist feminism. The narrative follows Dasiyah, a woman striving for autonomy and self-determination within the patriarchal constraints of the kretek industry and broader societal norms. Employing a descriptive-qualitative analysis, this research adopts an existentialist feminist framework to examine the series. Data were obtained through observation of the series and literature review relevant to the concept of women's existence in feminist theory. The analysis is conducted by examining how the female characters in Gadis Kretek are constructed in the narrative and how they negotiate their existential freedom. The results show that Dasiyah experiences various forms of limitations due to the patriarchal social structure, but she also shows resistance by asserting her existence as a free and independent individual. Her struggle reflects de Beauvoir's idea of how women can escape from the status of the Other and achieve authentic existence.